Safety of specific immunotherapy using an ultra-rush induction regimen in bee and wasp allergy - Andrzej Bożek; Krzysztof Kołodziejczyk (Taylor & Francis Group, 2018)
Background: Specific allergen immunotherapy to Hymenoptera venom (VIT) is a basic treatment for patients allergic to Hymenoptera venom. The aim of the study was to evaluate the safety of an ultra-rush regimen compared with the rush and conventional protocols. Materials and methods: In 31 patients with an allergy to bee venom and 82 with an allergy to wasp venom, the allergic adverse reactions during VIT were monitored. Patients were selected based on the criteria established by EAACI (European Academy of Allergy and Clinical Immunology) recommendations. Adverse reactions during the ultra-rush immunotherapy were measured, documented and classified according to the criteria of Mueller. Ultra-rush, rush or conventional protocols of the initial phase VIT using the Venomenhal vaccine (Hal Allergy, Leiden, Netherlands) were conducted. Results: Six (13.7%) patients on the ultra-rush regimen, 5 (14.3%) patients on the rush regimen and 9 (26.5%) on conventional VIT experienced an allergic reaction. There were no associations between the adverse allergic reactions and the following factors: gender, total IgE and allergen-specific IgE to wasp or bee venom before the VIT and cardiological drugs that were used. Conclusion: We found that the ultra-rush protocol (similar to the rush protocol) using the Venomenhal vaccine is safer than the conventional protocol.